I prodotti tipici agroalimentari italiani nel quadro della valorizzazione ambientale - Galvani, Adriana (Observatorio Medioambiental, 2002)
The increasing revenues in the developed countries is leading to a quantitative growth of consumers; in the food consumption instead is prevailing a trend to a qualitative growth, because of the dangerous illnesses aroused by adulterate foodstuffs. All this allows to appraise traditional and typical products originated in particular geographical areas. These products are now recognized by EU through the brands: DOC, DOCG, DOP, IGT. Italy can honour itself whit 112 recognized products; it is the second country after France according to the classification list of the Community. The first Italian region is Emilia Romagna with its worldwide famous Prosciutto di Parma, Parmigiano Reggiano, Aceto Balsamico. The products appreciation brings about an exploitation of traditions, handicraft and particularly of those lands where they originate from, stimulating a profitable rural tourism and gastronomic itineraries such as the «Route of wines and tastes» and the flavour routes on the Po Delta.